Effect of Degree of Milling (DOM) on Physicochemical and Nutritional Quality of Selected Rice Variety (BRRI dhan78) - Sharmin Akter; Rokeya Begum; Sharifa Sultana Dipti; Md. Abdul Alim; Somaiya Islam Shuchy; Habibul Bari Shozib; Md. Rakibul Hasan (International Journal of Food Science)
Rice, a staple for over half the global population, undergoes milling that removes bran and germ, impacting its nutrient content, physical properties, and glycemic response. The study was conducted to estimate the effects of the degree of milling (DOM) on the physicochemical, nutritional quality, blood glucose response (GR) and glycemic index (GI) of the BRRI dhan78. Rice samples collected from BRRI were milled at 0% (brown rice), 5% (partial milled), and 10% (full milled). Brown rice had the highest ash (1.3%), crude fiber (1.4%), protein (9.4%), and fat content (1.3%), while full milled rice had the highest moisture (11.1%) and carbohydrate content (79.7%). Thiamin content was affected by DOM in a linear fashion, declining from 0.15 mg/100 g to 0.13 mg/100 g as DOM increased. Significant reductions in Fe and Zn were observed as the DOM increased, from 8.6 mg/kg to 3.7 mg/kg and 22.0 mg/kg to 14.2 mg/kg, respectively. The length and breadth ratio increased along with the increase in DOM from 2.3 to 2.8. The L∗ and h values of different milled rice increased significantly (p<0.05) from 61.8 to 72.7 and 79.1 to 88.9, respectively, with increasing DOM, while a∗, b∗, and c∗ values significantly (p<0.05) decreased from 4.5 to 0.3, 23.4 to 14.0, and 23.8 to 13.6, respectively. Springiness and cohesiveness and of cooked rice significantly (p<0.05) increased from 0.2 to 0.5 and from 0.2 to 0.3, while hardness and chewiness decreased from 3.3×104 to 2.2×104 N/m2 and from 8.1×102 to 2.7×102 N/m2, respectively, with an increase in DOM. Full milled rice caused the highest glucose increase at different time intervals while brown rice caused the lowest. Brown rice had the lowest GI (54.4), while full milled rice had the highest GI (75.9). Brown rice was slightly liked, while partial milled rice was moderately liked. Both offer healthier benefits than full milled rice based on the DOM.